8-year follow-up after partial ex vivo resection of tumour in a single kidney followed by autotransplantation - Karczewski, Marek; Turkiewicz, Wojciech; Skowronek, Janusz; Karczewski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2011)
Radical nephrectomy (RN) in the treatment of renal cell carcinoma remains the “gold standard”, but sparing techniques (nephron sparing surgery, NSS), consisting of enucleation, partial nephrectomy or ex vivo resection, are increasingly gaining in importance. The techniques allow the achievement of better results, with a low rate of complications and mortality. Ex vivo resection is a technique which is becoming equivalent to radical nephrectomy. The risk of multifocal cancer ranges from 6.5 to 28%, whereas when the tumour has a diameter not exceeding 4 cm, the risk of multiplicity drops to 5%. The main risk involved in NSS is the possibility of recurrence in the ipsilateral kidney. The incidence of recurrence ranges between 0 and 10% and it is the lowest when the tumour has a low malignant potential and does not exceed 4 cm in diameter. Sometimes, due to the lack of the other kidney, this is the only opportunity that allows preservation of function of the remaining kidney. The paper describes a patient with a single kidney, affected by a tumour with a diameter of more than 5 cm, reaching the pyelocalyceal structure. Due to infiltration of the renal calyx, the ex vivo technique was adopted, allowing appropriate resection with an oncologically adequate margin and accurate supply of the urinary tract. The technique of surgery and the outcome of treatment in the very few cases described so far are discussed.